Terrestrial Groundwater Drives Coastal Ecosystem Shifts - D. Pratt; J. A. Guimond; E. S. Bacmeister; S. Fagherazzi; H. A. Michael (Geophysical Research Letters)
Abstract Saltwater intrusion (SWI) is accelerating along coastlines globally. This process is visually evident in low‐lying regions as conversion of forests and agricultural fields to saltmarsh. Marsh migration is largely attributed to ocean forcings such as sea‐level rise and storm surges. Here we show that terrestrial hydrology may also be a major driver of coastal ecosystem change. Data from the Delmarva Peninsula, USA show that declining upland groundwater head weakens the hydraulic gradient, causing shallow saline groundwater to push inland from coastal marshes. This drives SWI into coastal freshwater forests and farms at magnitudes that can exceed SWI from storms. We show that storm events often contribute to groundwater freshening through rainfall that restores the hydraulic gradient and flushes saline groundwater. Our findings highlight terrestrial groundwater as a primary control on root‐zone saltwater intrusion and suggest that changes in upland head may be a dominant, yet overlooked, driver of marsh migration.